Стан cудинної кальцифікації у хворих на хронічну хворобу нирок v стадії, що отримують лікування програмним гемодіалізом - Овська, Олена Геннадіївна; Садомов, Антон Сергійович; Овская, Е. Г.; Садомов, А. С.; Ovska, O. G.; Sadomov, A. S. (My University, 2013)
В статті представлені результати обстеження когорти гемодіалізних хворих для верифікації такого ускладнення як судинна кальцифікація. Визначена поширеність та розповсюдженість кальцифікації черевного відділу аорти методом мультизрізової комп’ютерної томографії та звичайної рентгенографії, також проведена низка лабораторних тестів та добове моніторування артеріального тиску. Під час дослідження встановлений кореляційний зв'язок різної сили між ступенем судинної кальцифікації з одного боку та діалізним стажем, САТ, ДАТ, ПАТ, сироватковими рівнями загального кальцію, фосфору та фосфорно-кальцієвого продукту з іншого боку. Дослідження продемонструвало, що судинна кальцифікація є поширеним ускладненням термінальної ниркової недостатності. Поперекова латеральна рентгенографія практично не поступається за інформативністю мультизрізовій комп’ютерній томографії у верифікації кальцифікації черевного відділу аорти. В статье представлены результаты обследования когорты гемодиализных больных для верификации такого осложнения как сосудистая кальцификация. Определена распространенность кальцификации брюшного отдела аорты методом мультисрезовой компьютерной томографии и обычной рентгенографии, также проведен ряд лабораторных тестов и суточное мониторирование артериального давления. В процессе исследования установлена корреляционная связь различной силы между степенью выраженности сосудистой кальцификации с одной стороны и диализным стажем, САД, ДАД, ПАД, сывороточными уровнями общего кальция, фосфора и фосфорно-кальциевого продукта с другой стороны. Исследование показало, что сосудистая кальцификация является распространенным осложнением терминальной почечной недостаточности. Поясничная латеральная рентгенография практически не уступает по информативности мультисрезовой компьютерной томографии в верификации кальцификации брюшного отдела аорты. Numerous cross-sectional studies on general population and chronic kidney disease (CKD) patients demonstrate relationships between cardiovascular calcification and bone disorders, including osteoporosis, osteopenia and high or low bone activity. The mechanisms of relationships in the "bonevessel" system are due to the presence of common factors that affect bone remodeling and vascular calcification (VC) and also participation of bone cells in structural and functional reorganization of vessels. The nature of these links is not well understood and could result from: 1) common factors acting on bone remodeling and vascular arterial calcification; 2) compromised bone blood supply responsible for arteriosclerosis of bone vessels and reduced perfusion; and/or 3) direct action of bone cells (osteoblasts/osteocytes) on vascular biology and structure. Mechanisms of VC in CKD are not still fully understood. There are no standardized approaches to the diagnostics of VC in CKD. At present to verify VC radiographic methods are used. Some researchers propose to visualize VC using conventional X-rays of hands, pelvic region, abdomen. For visualization of coronary artery calcification is better to use electronic wave multislice and computed tomography (MSCT). The strongest correlation, according to foreign studies, was found between coronary artery calcification and calcification of the abdominal aorta. The aim of our research was to study VC in patients with stage V of CKD, who are treated by program hemodialysis (HD) .
Состояние сосудистой кальцификации у пациентов с хронической болезнью почек v стадии, которые получают программный гемодиализ
Vascular calcification in patients with chronic kidney disease who are treated by program hemodialysis.
Keywords: хронічна хвороба нирок; програмний гемодіаліз; судинна кальцифікація; артеріальна гіпертензія; хроническая болезнь почек; программный гемодиализ; сосудистая кальцификация; артериальная гипертензия; chronic kidney disease; program hemodialysis; vascular calcification; arterial hypertension